Performance Analysis of the 2 MW Diesel Engine Generator as an Additional Power Plant at PT. Indolakto Purwosari - Bian Irianti; Andriyanti, Aulidina Dwi Nur (PT FORMOSA CENDEKIA GLOBAL, 2024)
Fluctuations in electricity demand can lead to inefficiencies in diesel generators (DEG) and potentially trigger blackouts, as experienced by PT Indolakto. This study aims to identify the performance parameters of a 2 MW DEG and formulate strategies to prevent blackouts caused by the 2 MW DEG at PT Indolakto. The research used data collection techniques including field observations, interviews, literature studies, and performance test analysis. The results showed that the efficiency of the 2 MW DEG at load reached 44%, indicating there is still reserve power. An overload of 21% from the generator's capacity resulted in a blackout and a system frequency drop of 13.4 Hz from the normal frequency. Although the 2 MW DEG has adequate efficiency, optimization is necessary to prevent blackouts. One strategy is to use the 2 MW DEG as a system reserve for critical loads.